2017
DOI: 10.1002/anie.201610240
|View full text |Cite
|
Sign up to set email alerts
|

Photoproduction of Hydrogen by Decamethylruthenocene Combined with Electrochemical Recycling

Abstract: The photoinduced hydrogen evolution reaction (HER) by decamethylruthenocene,C p 2 *Ru II (Cp* = C 5 Me 5 ), is reported. The use of am etallocene to photoproduce hydrogen is presented as an alternative strategy to reduce protons without involving an additional photosensitizer.T he mechanism was investigated by (spectro)electrochemical and spectroscopic (UV/Vis and 1 HNMR) measurements.T he photoactivated hydride involved was characterized spectroscopically and the resulting [Cp 2 *Ru III ] + species was electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 20 publications
5
46
0
Order By: Relevance
“…The uses of ferrocene derivatives [1], decamethylferrocene [2], cyclopentadienylcobalt phosphine [3], cobaltocene [4], molybdocene [5], osmocene [6] or ruthenocene [7] as electron donors for hydrogen evolution reaction (HER) have been reported. In the case of osmocene and ruthenocene, the HER was carried out under light exposure.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The uses of ferrocene derivatives [1], decamethylferrocene [2], cyclopentadienylcobalt phosphine [3], cobaltocene [4], molybdocene [5], osmocene [6] or ruthenocene [7] as electron donors for hydrogen evolution reaction (HER) have been reported. In the case of osmocene and ruthenocene, the HER was carried out under light exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that light driven HER also occurs at a polarized ITIES in the presence of decamethylruthenocene (DMRc) [7]. DMRc due to its only moderately low redox potential is thermodynamically a weak electron donor for HER, however, in the presence of UV light it is capable to reduce protons dissolved in DCE [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations